تحول مفهوم الأمن بعد الحرب الباردة - مجيدي, يحي; فودي, مصطفى كمال (University of Eloued جامعة الوادي, 2018)
عرف التنظير في العلاقات الدولية اتجاهات عدة مما أدى إلى تحول مفهوم الأمن من حيث الأطر والأنساق لكي يكون أكثر تكيف مع تحولات النظام الدولي لما بعد الحرب الباردة التي أفرزت بدورها عن فواعل جديدة في السياسة الدولية. دخلت الدراسات الأمنية لحقل العلاقات الدولية حيث أصبحت محل اهتمام الباحثين والمفكرين بغرض تفسير التحول الابستمولوجي الذي طرأ على حقل العلاقات الدولية.The theorization in IR witnessed a number of trends that took an important path to change the security’s notion to be more compatible with the international order transformation on the post-cold war which in turn provided new actors and factors in the field of international politics. Research studies on security reached a new frame-work which became a particular concern to the researches for the sake of clarity and explanation of the epistemological transformation that had taken place in the IR.
The transformation of security concept post-cold war
مقال
Keywords: الأمن – الحرب الباردة- العلاقات الدولية- النظريات.; Security - Cold War - International Relations - Theories.